Metabolism of Rhizobium bacteroids - Lodwig, E; Poole, P (Taylor and Francis, 2003)
Nitrogen fixation within legume nodules results from a complex metabolic exchange between bacteria of the family Rhizobiaciae and the plant host. Carbon is supplied to the differentiated bacterial cells, termed bacteroids, in the form of dicarboxylic acids to fuel nitrogen fixation. In exchange fixed nitrogen is transferred to the plant. Both the bacteroid and the plant derived peribacteroid membrane tightly regulate the exchange of metabolites. In the bacteroid oxidation of dicarboxylic acids via the TCA cycle occurs in an oxygen-limited environment. This restricts the TCA cycle at key points, such as the 2-oxoglutarate dehydrogenase complex, and requires that inputs of carbon and reductant are balanced with outputs from the TCA cycle. This may be achieved by metabolism through accessory pathways that can remove intermediates, reductant or ATP from the cycle. These include synthesis of the carbon polymers PHB and glycogen, and bypass pathways such as the recently identified 2-oxoglutarate decarboxylase reaction in soybean bacteroids. Recent labelling data has shown that bacteroids synthesise and secrete amino acids, which has led to controversy over the role of amino acids in nodule metabolism. Here we review bacteroid carbon metabolism in detail, evaluate the labeling studies which relate to amino acid metabolism by bacteroids, and place the work in context with the genome sequences of Mesorhizobium loti and Sinorhizobium meliloti. We also consider a wider range of metabolic pathways, which are probably of great importance to rhizobia in the rhizosphere, during nodule initiation, infection thread development and bacteroid development.